Current and future transboundary water cooperation over the YarlungZangbo/Brahmaputra River basin: from an interdisciplinary perspective - He, Yanmei (Water policy, 2021)
While all riparian states in the YarlungZangbo/Brahmaputra River basin have conducted or planned dam-building, water diversion or other water-related activities to meet their respective national policy goals, they are also undertaking fragmented cooperation to solve conflicts and disputes as they arise. Mainly using a combination of natural, economic, social, environmental, political and legal factors affecting transboundary water cooperation as its analytical framework, this article explores the features of the current cooperation practice among the riparian states, then analyses manifold challenges the practice faces. The author lastly envisions an available path where all riparian states develop multilateral cooperation to address the challenges in the future. This article suggests that the rationale for future cooperation is the policy of preventive diplomacy with the aim of avoiding water conflicts and significant transboundary harm; the basic prerequisite for future potential cooperation is trust building among the riparian states, especially between China–India and between India–Bangladesh; the suitable form of future cooperation is expected to be an inclusive, comprehensive and coordination-oriented River Basin Organization; and the focus areas for future cooperation are supposed to be data sharing and riparian activities that all or most of the riparian states are suffering from.